Physical-chemical characterization of quinoa (Chenopodium quinoa Willd.), amaranth (Amaranthus caudatus L.), and chia (Salvia hispanica L.) flours and seeds (2018)
Quinoa, amaranth, and chia flours have considerable amounts of protein, starch, dietary fiber, lipids, minerals, vitamins, and bioactive components, which provide in them exceptional properties for human nutrition. The aim of this research was the physical-chemical characterization of quinoa, amaranth, and chia flours and seeds through proximal, optical, functional, thermal, and structural analyses. From the results obtained during the proximal analysis, considerable proportions were determined of protein and fiber for the three flours, with the highest values in chia flour at 28.56% and 39.8%, respectively. These results were corroborated by optical microscopy analysis performed on longitudinal cuts in the three types of seeds. Thermal parameters indicated that the three flours presented irreversible thermal degradation processes and glass transition change for amaranth and chia flours at temperatures above 100ºC. Structural characterization of the flours via FTIR have allowed detecting differences in protein and lipid characteristic absorption bands. Diffraction patterns of type A starch were identified for quinoa and amaranth flours, while the chia flour had two crystalline peaks corresponding to calcium and magnesium. Scanning electron microscopy images showed starch aggregates in the quinoa flour, a complex structure composed of spherical proteins that surround the starches in amaranth flour and fibrous structures and spherical proteins in chia flour.